The demographic and economic transition in Central and Eastern Europe: Management implications - Manfred Perlitz; Lasse Schulze; Christina Benita Wilke (Journal for East European Management Studies, 2010)
Although the population in Central and Eastern European Countries (CEEC) is still younger, on average, than in Western Europe, the CEEC also have to cope with challenges caused by the demographic shift towards an ageing, shrinking population. Some countries are ageing even faster than Western Europe. Apart from ageing, the CEEC also have to face problems caused by the economic transition. Based on neo-institutional organisation theory this paper looks at the management implications of these developments and points out strategies for Human Resources Management and Marketing in how to cope with upcoming challenges. – – Obwohl die Bevölkerung im Durchschnitt jünger als in Westeuropa ist, haben auch die Mittel- und Osteuropäischen Länder (MOEL) die Herausforderungen der demographischen Entwicklung durch eine alternde und schrumpfende Bevölkerung zu bewältigen. Manche Länder altern sogar noch schneller als Westeuropa. Neben der Alterung haben die MOEL auch Probleme des ökonomischen Übergangs zu verkraften. Dieser Artikel betrachtet - basierend auf dem neo-institutionalistischem Ansatz der Organisationstheorie - die Implikationen dieser Entwicklungen für das Management und zeigt Strategien für das Personalmanagement und Marketing auf, um diese bevorstehenden Herausforderungen zu bewältigen.
Keywords: 650; Demography; Neo-Institutional Organisation Theory; Human Resources Management; Marketing; Pension Reform